Type II D Phalangeal Neck Fractures in Children: A Series of 20 Cases Treated According to a Preset Stepwise Algorithm - Al-Qattan, Mohammad M.; Almohrij, Saad A.; Alaskar, Batool; Alhassan, Turki S. (Journal of Hand and Microsurgery, 2020)
Introduction Type II phalangeal neck fractures are defined as displaced fractures with bone-to-bone contact at the fracture site. In the type II D subtype, the distal fracture fragment is thin. A review of the literature did not reveal any study investigating the outcome of management of these fractures.Patients and Methods This is a retrospective study of 20 consecutive children with type II D phalangeal neck fractures treated over the past 4 years. Demographic data were reviewed. All cases were managed according to the preset stepwise algorithm. The outcome of management at final follow-up was documented using Al-Qattan’s grading system.Results The mean age was 30 months (range 12–80 months). There were 12 males and 8 females. The mean follow-up was 2 years (range 7 months to 3 years). The largest two categories within the management algorithm were patients with minimally displaced fractures treated conservatively (n = 8) and those with displaced fractures treated with closed reduction and percutaneous K-wire fixation (n = 9). Fischer exact test was used to compare the outcome in these two groups and the p value was significant (p = 0.015), indicating a significantly better outcome in the former group.Conclusion Several conclusions were made from the study. Type II D of phalangeal neck fractures tend to occur in young children and the majority involve the middle phalanx. The thinness of the distal fracture fragment makes standard techniques of closed reduction more difficult. However, flexion of the proximal and distal joints appears to be effective in reducing dorsally displaced type II D fractures by closed means. Finally, a more conservative approach to minimally displaced type II D fractures results in a better outcome compared with closed reduction and percutaneous K-wire fixation.
Keywords: type II D; phalangeal neck fractures; hand fractures; children; algorithm of management